KELAYAKAN PEMAKAIAN INSTALASI LISTRIK 450 VA SETELAH PEMAKAIAN 10 TAHUN - Muratno .; Yeheskiel Lolopayung (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2014)
A good quality of electrical installation is higly dependent on the implementation of thestandard electrical installation regulation namely PUIL 2000. Considering in principle the goalof enforcement for the security op people, goods and supply of electricy that is safe andsufficient. But after a certain period of electrical installation is expected to experiencechanges in both quality and quantiry. Based on that, the researchers conducting research,aiming to determine the feasibilityof using home lighting installation in use for more than 10years as many as 104 homes with a capacity of 450 VA at Keerom District West Koya, thisresearch will reveal the five indicators that include the installation of home insulationresistence, cross cable, grounding resistance, the conditionof the home installation andsecurity installation (MCB). Data collection tecnigues used include : measurement techniqueusingmeasuring instrument called a megger and ingsut ruler, measurement and observationof the five indicators in each home installation and data analysis techniques used wereanalytical scoring ( rating ).Results of measurement, observation and analysis of scoring on each indicator of homelighting installation and compared with standard values of PUIL 2000 incude : the level ofinstallation resistence feasibility and feasibility level of cable cross-section consideredunsuitable for use reaches 100% feasibility levelinstallationconditions for all lightinginstallations of 104 houses only 43 homes that are considered unsuitable for usereached41,34 %, and 61 homes are considered not suitable to be used to reach 58,65 % feasibilitylevel of safety installation that are considered imporer wear rate reached 59,61 % and thefeasibility of gorundingresistence for all home lighting installation is not used and areconsidered not suitable to be used to reach 0% . it can be concluded that the level ofhomelighting installation feasibility of the five indicators that is not feasible to use many as 42houses to reach 40,38 % and feasibility level home lighting installation is consideredunsuitable for use as many as 62 housesto reach 59,61 %